Environment for teaching and development of mobile robot systems - Alves, Silas; Rosário, João Maurício; Ferasoli Filho, Humberto [UNESP]; Pegoraro, Renê [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Using robots for teaching is one approach that has gathered good results on Middle-School, High-School and Universities. Robotics gives chance to experiment concepts of a broad range of disciplines, principally those from Engineering courses and Computer Science. However, there are not many kits that enables the use of robotics in classroom. This article describes the methodologies to implement tools which serves as test beds for the use of robotics to teach Computer Science and Engineering. Therefore, it proposes the development of a flexible, low cost hardware to integrate sensors and control actuators commonly found on mobile robots, the development of a mobile robot device whose sensors and actuators allows the experimentation of different concepts, and an environment for the implementation of control algorithms through a computer network. This paper describes each one of these tools and discusses the implementation issues and future works. © 2010 IEEE.
Keywords: Computer science; Engineering; Robotics; Teaching; Computer science and engineerings; Control actuators; Control algorithms; Engineering course; Low cost hardware; Mobile robot systems; Sensors and actuators; Actuators; Algorithms; Automobile electronic equipment; Automobile parts and equipment; Computer hardware; Equipment testing; Experiments; Mechanics; Mobile robots; Sensors